2018
DOI: 10.1007/s00246-018-1912-x
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Systolic Function Parameters in Hypoplastic Left Heart Syndrome

Abstract: Assessment of the systolic function of the right ventricle (RV) in patients with hypoplastic left heart syndrome (HLHS) is important. The asymmetric shape and heavy trabeculations make accurate assessment of RV systolic function challenging. Novel measures of RV function could be helpful in distinguishing reduced versus preserved function in HLHS and may also be worse in HLHS with preserved function compared to normal controls. These novel methods offer promise, but research and clinical applicability is hinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…This retrospective observational study of patients with single ventricle heart disease after Fontan operation demonstrates that markers of ventricular performance are decreased compared to known normative values of healthy patients and that global longitudinal strain rate and global circumferential strain rate worsen over the decade following the Fontan operation, even without an overt change in the qualitative assessment of ventricular function 9,16,18–20 . Not surprisingly, the aggregate mean values for most functional parameters were worse than what would be expected for a healthy age‐matched population without heart disease 9,11,15,18,19,21 . While there was a marginal improvement in the s/d ratio improved over time, this change was most likely related to the known decrease in heart rate as these children get older, and not related to a true change in ventricular function 17 .…”
Section: Discussionmentioning
confidence: 83%
“…This retrospective observational study of patients with single ventricle heart disease after Fontan operation demonstrates that markers of ventricular performance are decreased compared to known normative values of healthy patients and that global longitudinal strain rate and global circumferential strain rate worsen over the decade following the Fontan operation, even without an overt change in the qualitative assessment of ventricular function 9,16,18–20 . Not surprisingly, the aggregate mean values for most functional parameters were worse than what would be expected for a healthy age‐matched population without heart disease 9,11,15,18,19,21 . While there was a marginal improvement in the s/d ratio improved over time, this change was most likely related to the known decrease in heart rate as these children get older, and not related to a true change in ventricular function 17 .…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, these data illustrate the potential of atrial deformation parameters, which may act as predictors for the necessity of therapeutic interventions in adult cardiology [20]. Besides already investigated potential function of 2D-STE to distinguish between healthy fetuses and fetuses with congenital heart diseases (CHD), the function of myocardial strain as a predictor for the success of cardiosurgical interventions may be a potential usage for 2D-STE [21,22]. To enable future research in these areas, the aim of our study was to evaluate atrial and ventricular MF using 2D-STE in normal fetal cardiac 4-chamber view (4CV), which is a common standard in basic sonographic screening, and test reproducibility of our collected deformation values.…”
Section: Recent Evaluation Of Deformation Values By 2d-stementioning
confidence: 78%
“…In contrast, a recently published work showed a significant association between RV function before and after stage I of the Norwood operation. Zaidi et al observed a significant reduction in echocardiographic functional parameters after surgery as well as a correlation with the length of hospital stay, the need for extracorporeal membrane oxygenation, and the mortality rate of HLHS children 37 , 38 .…”
Section: Reviewmentioning
confidence: 99%